Family Resilience Model of Early Marriage Couples in Preventing Domestic Violence and Child Violence - Radhiah, Sitti; Daswati, Daswati; Munir, Ardi; Rahman, Abd (TAZKIYA Journal of Psychology, 2025)
Early marriage is linked to high stress due to the developmental immaturity of young couples, which hinders conflict resolution and future planning. This often leads to divorce and, when combined with parenting stress, may increase the risk of domestic violence and child abuse. The Office of Women's Empowerment and Child Protection (DP3A) of Central Sulawesi Province in 2023 recorded 144 cases of violence against women and children. This study aims to determine the Family Quality Index (FQI) in early married couples and analyze the effect of individual resilience on family resilience, by predicting it through parenting stress. This type of research is a quantitative analytic survey with SEMPLS analysis. The research sample was 210 early married couples who have children, who directly care for children, selected using probability proportionate size technique. The results of the Family Quality Index research of early marriage couples show that the quality dimension of structural legality is in the very high category, the socio-cultural quality dimension is in the medium category, while the dimensions of physical, economic and socio-psychological resilience are in the very low category, while the results of SEMPLS analysis show that there is a positive and significant effect of husband's resilience and wife's resilience on parenting stress, as well as parenting stress on family resilience, but there is no positive and significant effect of husband's resilience or wife's resilience on family resilience. These results suggest that the relationship between individual resilience and family resilience is fully mediated by parenting stress. The family resilience model shows valid and reliable results and a fit model. Conclusions: The findings confirm the important role of parenting stress as a mediator in the relationship between individual resilience and family resilience in early marriage couples. The model developed is not only valid and reliable, but can also be the basis for family-based interventions. The urgency of strengthening integrated premarital counseling services for adolescents to improve parenting role readiness and prevent the risk of family violence is emphasized.